MECHANISMS FOR DEVELOPING THE COMPETENCE OF NATIONAL PRIDE OF FUTURE TEACHERS ON THE BASIS OF INTEGRATIVE APPROACHES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article used the criteria and indicators for the development of the competence of civil and national pride in future teachers as indicators of the assessment of upbringing in the introduction of the “concept of continuous spiritual education”. As a result, the possibility of diagnosing future educators in student’s readiness to form a competence of national pride has increased. These proposals made it possible to prepare future educators for educational activities, to develop an active civic position in them.